2019
DOI: 10.1021/acs.iecr.9b01644
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Impact Toughness of Renewable Poly(lactic acid)/Thermoplastic Polyurethane Blends via Constructing Cocontinuous-like Phase Morphology Assisted by Ethylene–Methyl Acrylate–Glycidyl Methacrylate Copolymer

Abstract: Poly­(lactic acid) (PLA)/thermoplastic polyurethane (TPU) blends and their ternary blends with the incorporation of ethylene–methyl acrylate–glycidyl methacrylate copolymer (E–MA–GMA) were prepared by melt blending. The PLA/TPU (70/30) blend exhibited optimum elongation at break of 615% and impact strength of 53.6 kJ/m2. Compared with PLA/TPU (90/10) blend, the impact strength of PLA/TPU/E–MA–GMA (80/10/10) blend increased by more than 15 times; meanwhile, the elongation at break did not suffer apparent reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 76 publications
(179 reference statements)
1
37
0
Order By: Relevance
“…The characteristic peak of the −CH 3 appears at 2850 cm –1 and the peaks of epoxy group locate in 844 and 911 cm –1 for EMA–GMA. 35,36…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peak of the −CH 3 appears at 2850 cm –1 and the peaks of epoxy group locate in 844 and 911 cm –1 for EMA–GMA. 35,36…”
Section: Resultsmentioning
confidence: 99%
“…The chemical and physical features of PLLA play an important role in the ultimate performance prole of the multiphase blends: (1) the crystalline domains of PLLA with high modulus and their orientation behaviors under applied force can reinforce the blends with increased tensile strength and toughness; [37][38][39] (2) the amorphous parts facilitate the formation of hydrogen bonds with polyurethane and the ordering of the amorphous phase is responsive and tunable under tension, which are effective in toughening polyurethane. 37,40 Translucent polymer blends PU/PLLAs with varied ratios of PLLA from 0 to 20 wt% were prepared via the solution casting method (details of the preparation are described in ESI, Table S1 †). The transparency of the blends decreased with the increase of the crystalline PLLA content ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The TPV manifested an approximately co-continuous morphology with vulcanized UPE compactly dispersed in PLA matrix. 38 Other studies have reported the similar discovery about the co-continuous structure in the super-tough PLA-based composites obtained by melt blending, 32,[39][40][41][42] which is dissimilar from the classic "sea-island" structure.…”
Section: Introductionmentioning
confidence: 86%
“…This is usually obtained by functionalization of modifier polymer and/or the use of a third component as a compatibilizer in the blend system. [25][26][27][28][29][30][31][32][33][34][35][36][37] Mazidi et al found that polymethylmethacrylate (PMMA) can effectively tune the interfacial interaction of incompatible PLA/polybutadiene-g-poly (styrene co-acrylonitrile) (PB-g-SAN)…”
Section: Introductionmentioning
confidence: 99%